(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
It is already well-known that the vast energy available in ocean waves can provide a massive contribution towards effective decarbonisation. Nonetheless, due to the irregular reciprocating motion of ocean waves, convergence towards a single type of technology becomes rather difficult, and tailored research, aiming at ultimately providing reliable WEC systems, is still required to achieve commercialisation. Once a given concept is established, numerical models become almost automatically required for a (very) large variety of tasks, including e.g. dynamical and performance assessment, control technology, geometry optimisation, and mooring design, among others. Depending on the requirements associated with a specific task, different types of models are used, with very different levels of complexity (both computational and analytical) and fidelity. For instance, a fully nonlinear estimation of the hydrodynamic response of a WEC would often require high-fidelity numerical modelling techniques, based on e.g. computational fluid-dynamics (CFD), while control applications prefer analytical expressions able to capture the main underlying dynamics in a simplified form. Regardless of the associated complexity, validation is always required for the reliable utilisation of a specific model for a given application, with experimental validation being the most valuable tool to secure this objective. In recent years, different initiatives were put in place, aiming at the identification of numerical model accuracy through a set of widely available case studies. For instance, the OES-Task 10 has been running a number of experiments followed by blind numerical model validations for several single-body wave energy converters. While the proposed methodologies proved to be efficient, the cases under study are all focused on single-body devices. Since the sector is slowly approaching a pre-commercial stage, it is important to prove the capabilities of numerical models also for farm configurations which are, ultimately, the way in which WEC systems will be effectively deployed. Motivated by this, we present, in this paper, an overview of an experimental campaign performed at Aalborg University during the period of September-October 2021, where 8 different array layouts of up to 5 devices have been tested, using a 1:20 prototype of the Wavestar WEC system as a baseline device (see PDF file for reference). Data has been collected systematically for regular and irregular wave conditions, including e.g. free-surface elevation at different points in the wave tank (with 19 wave probes in place), effective wave excitation forces acting on each device and layout, and associated motion variables. Furthermore, each different layout has been also tested under (reactive) controlled conditions, providing experimental data on PTO forces and associated motion (i.e. under controlled conditions). The results of this experimental campaign will be available as part of an Open-Access dataset, being an extremely valuable tool for reliable modelling within the WEC research/industrial community. This paper intends to provide a detailed account of the technical aspects concerning the full experimental campaign, including setup, test design, synergies between collected data, and examples of how these results can be used to validate a variety of models, from different input/output points, depending on the requirement of each specific application.